2021
DOI: 10.1097/md.0000000000024643
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics in patients with coronary slow flow phenomenon

Abstract: Coronary slow flow phenomenon (CSFP) is a coronary artery disease in which coronary angiography shows no obvious stenosis, but there is a delay in blood flow perfusion. The etiopathogenic mechanisms of CSFP are still unclear. The aim of the present study was to investigate the role of clinical characteristics in patients with CSFP, and to provide a reference for exploring the potential mechanisms of CSFP. Patients with angiographically normal epicardial arteries were enrolled (145 patients with CSFP and 145 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
1
1
Order By: Relevance
“…The study reported an insignificance difference between the two groups regarding the age, the gender, the BMI, and hypertension. In contrast to our findings, Huang et al [12] study included patients with normal epicardial arteries angiographically (145 patients with CSFP and 145 normal controls). Clinical data and laboratory indices were collected and analyzed prior to coronary angiography using peripheral venous blood samples.…”
Section: Discussioncontrasting
confidence: 98%
“…The study reported an insignificance difference between the two groups regarding the age, the gender, the BMI, and hypertension. In contrast to our findings, Huang et al [12] study included patients with normal epicardial arteries angiographically (145 patients with CSFP and 145 normal controls). Clinical data and laboratory indices were collected and analyzed prior to coronary angiography using peripheral venous blood samples.…”
Section: Discussioncontrasting
confidence: 98%
“…16 Increasing evidence indicates that patients with CSFP are prone to atherosclerosis and obstructive CAD. 43,44 Consistent with these findings, the MAPH score was identified as a significant indicator in distinguishing both the presence and the severity of CAD, exhibiting better diagnostic performance than LSR and HSR. Moreover, the regression model incorporating the MAPH score explained a higher variance of CAD compared to the regression models that included the LSR and HSR indices.…”
Section: Discussionsupporting
confidence: 56%
“…Xia et al (25) concluded that coronary slow flow may be equally prevalent between males and females and a study by Huang et al (26) concluded that there is no substantial difference in age, smoking, hypertension, DM as well as blood pressure measurements between patients having coronary slow flow and control patients.…”
Section: Discussionmentioning
confidence: 99%